Adrenergic action in breast cancer - Luthy, Isabel Alicia (2012)
Breast cancer is the most frequent malignancy in women in the majority of western countries. Both acute and chronic stress cause the release of epinephrine and norepinephrine. These natural cateholamines bind to nine different adrenoceptors. Breast cancer epithelial cells express α2 and β2-adrenoceptors. Catecholamine binding to α2-adrenoceptors in cancer cells is associated with increased cell proliferation. On the contrary, catecholamine binding to β2-adrenoceptors result in diminished cell proliferation. Therefore, the relative concentration of these receptors in the tumor cell will enhance or diminish proliferation. Also in vivo, following stimulation with natural catecholamines, the tumor will experience enhanced or diminished growth depending on the relative concentration of α2 and β2-adrenoceptors. The administration of synthetic α2-adrenergic agonists enhances tumor growth whereas the administration of the α2-adrenergic antagonist rauwolscine diminishes tumor growth below control levels, behaving as an inverse agonist. The administration of β- adrenergic agonists could also be useful to lower tumor growth. The use of β-blockers in patients have been described by several groups as very promising specially in the case of the HER2 positive and triple negative tumors. Thus different therapeutic compounds targeting adrenergic receptors could become very important drugs for the treatment of selected cancer patients. Currently, adrenergic agonists/antagonists are used for the treatment of different diseases and have minimal side effects when compared with chemotherapy. The possibility of using them for treatment of breast cancer is an encouraging concept especially for the patients with resistance to the usual anti-cancer therapy.